Soup to Tree: The Phylogeny of Beetles Inferred by Mitochondrial Metagenomics of a Bornean Rainforest Sample - Crampton-Platt, Alex; Timmermans, Martijn J T N; Gimmel, Matthew L; Kutty, Sujatha Narayanan; Cockerill, Timothy D; Vun Khen, Chey; Vogler, Alfried P (Molecular biology and evolution, 2015)
In spite of the growth of molecular ecology, systematics and next-generation sequencing, the discovery and analysis of diversity is not currently integrated with building the tree-of-life. Tropical arthropod ecologists are well placed to accelerate this process if all specimens obtained through mass-trapping, many of which will be new species, could be incorporated routinely into phylogeny reconstruction. Here we test a shotgun sequencing approach, whereby mitochondrial genomes are assembled from complex ecological mixtures through mitochondrial metagenomics, and demonstrate how the approach overcomes many of the taxonomic impediments to the study of biodiversity. DNA from approximately 500 beetle specimens, originating from a single rainforest canopy fogging sample from Borneo, was pooled and shotgun sequenced, followed by de novo assembly of complete and partial mitogenomes for 175 species. The phylogenetic tree obtained from this local sample was highly similar to that from existing mitogenomes selected for global coverage of major lineages of Coleoptera. When all sequences were combined only minor topological changes were induced against this reference set, indicating an increasingly stable estimate of coleopteran phylogeny, while the ecological sample expanded the tip-level representation of several lineages. Robust trees generated from ecological samples now enable an evolutionary framework for ecology. Meanwhile, the inclusion of uncharacterized samples in the tree-of-life rapidly expands taxon and biogeographic representation of lineages without morphological identification. Mitogenomes from shotgun sequencing of unsorted environmental samples and their associated metadata, placed robustly into the phylogenetic tree, constitute novel DNA "superbarcodes" for testing hypotheses regarding global patterns of diversity.
Keywords: brouci; Phylogeny; deštný prales; Genome, Mitochondrial; Mitochondria; Gene Frequency; metagenom; zvířata; genetická variace; genom mitochondriální; Sequence Analysis, DNA; Rainforest; Borneo; Genes, Insect; mitochondrie; vysoce účinné nukleotidové sekvenování; Contig Mapping; kontigové mapování; Coleoptera; hmyzí geny; frekvence genu; Genetic Variation; sekvenční analýza DNA; Animals; Metagenome; fylogeneze; High-Throughput Nucleotide Sequencing